2007
DOI: 10.1177/000313480707301118
|View full text |Cite
|
Sign up to set email alerts
|

Can Acute Appendicitis be Treated by Antibiotics Alone?

Abstract: Emergency appendectomy at presentation has been the standard of care for acute appendicitis. We examined the use of antibiotics as an alternative treatment. From September 2002 to August 2003, 170 consecutive patients diagnosed with acute appendicitis without abscess were reviewed retrospectively. Patients were divided into two groups: Group I (n = 151) underwent emergency appendectomy and Group II (n = 19) received antibiotics alone. The mode of treatment was at the attending surgeon's discretion. The overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…A negative appendicectomy is particularly hampered with problems5. Therefore in recent years there has been increased interest in antibiotic therapy as primary treatment6, and several studies have indicated that perforated appendicitis in children can be treated with antibiotics7–9. In addition, retrospective studies in adults with perforated appendicitis treated conservatively suggested that late recurrences exhibited a mild clinical course10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…A negative appendicectomy is particularly hampered with problems5. Therefore in recent years there has been increased interest in antibiotic therapy as primary treatment6, and several studies have indicated that perforated appendicitis in children can be treated with antibiotics7–9. In addition, retrospective studies in adults with perforated appendicitis treated conservatively suggested that late recurrences exhibited a mild clinical course10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into novel and efficient antibiotics have also provided new opportunities for nonsurgical treatment of appendicitis ( 8 ). Antibiotic therapy, the main nonoperative therapy, is becoming increasingly important in the treatment of acute appendicitis ( 9 , 10 ). Previous studies have shown that perforated appendicitis in children may be treated with antibiotics ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…From all the meta-analyses included, there were eight different individual studies, in different combinations [ 20 27 ], with the majority being prospective studies (87.5 %). Only one meta-analysis included a retrospective study [ 23 ].…”
Section: Resultsmentioning
confidence: 99%